The Green Construction Model in the Construction Industry to Support a Sustainable Green Economy - Dhea Agusty Ningrum; Tomy Sun Siagian; MHD. Andi Rasyid (SEAN Institute, 2024)
This research aims to test and analyzeThe Green Construction Model in the Construction Industry to Support a Sustainable Green Economy. The type of research used in this research is descriptive quantitative research method. This research also includes quantitative research that is correlational in nature. The population in this research is the Medan City construction management company. The sample in this research was construction projects in the city of Medan which were taken using a random sampling method with the acquisition of 50 construction projects in the city of Medan. This study consists of independent variables namelygreen constructionwhile the dependent variable isgreeneconomyas well asgreen social workas a moderating variable. The data analysis technique used in this research is descriptive analysis, variance-based Structural Equation Modeling (SEM) analysis (Partial Least Square). The research results show that the implementation of green construction in construction companies in Medan City has an impact of 72.6% on achieving a sustainable green economy. with the involvement of social workers (Green social work) gives an increase of 18.4%. This increase can be achieved due to the various roles carried out by social workers in efforts to preserve the environment as well as with the aim of sustainable social welfare, one of which is as a facilitator, educator, motivator, mediator and initiator in environmental conservation.